A Review Paper on Adapting Agriculture to Climate Change (International Journal of Innovative Research in Engineering & Management, 2023)
The urgency of tackling agricultural  adaptation is heightened by the significant trends in  climate change currently visible, the probability of  additional changes, and the growing magnitude of  possible climatic effects more logically. There are many  possibilities for adaption accessible for minor alterations  to current agricultural systems, frequently; current climate  risk management is modified. We demonstrate that  putting these ideas into action is likely to affect some  agricultural systems that will benefit from mild climate  change. However, their efficacy is limited in situations  that are more complex. Climate change is becoming more  severe. As a result, additional systemic resource  adjustments are required. Targeted diversification, for  example, must be addressed when allocating resources of  lives and production systems. We believe that obtaining  increased adaptation activity will require climate change  integration climate change-related problems with  additional risk factors with other policy domains, such as  variability and market risk, and other policy domains,  such as long-term development. Dealing with the  numerous obstacles to effective adaptation will require a  multifaceted and dynamic approach.
Keywords: Adaptation; Cropping; Forestry; Grazing